The life and times of Kama Chungwa, 1798-1875 - Yekela, Drusilla Siziwe (Rhodes University, Faculty of Humanities, Department of History, 1989)
Few students of History understand the derivation and/or origin of the Gqunukhwebe oath "Ndifung' uChungw' efel' ennyameni: I swear by Chungwa who is lying dead at Mnyameni (Alexandria)." A desire to eludicate this point and other related facts inspired me to undertake a close examination of the history of the Gqunukhwebe people, selecting as my main theme the life-work of Chief Kama. In the first chapter I am discussing the creation of the Gqunukhwebe Chiefdom under Khwane by the Xhosa King, Tshiwo. The central theme here is the Black-White confrontation of the 17th - 18th centuries on the Cape Eastern Frontier. As a result of the collision the Gqunukhwebe people were forced to make a home on the banks of the Thwecu River along the east coast. It was here that Kama reached early manhood. The second chapter describes the establishment of Wesleyville Missionary Station by William Shaw in 1823, the first Methodist Missionary Institution in all Xhosaland. In chapter three the discussion centers on the significance of Kama's conversion. An unforeseen outcome of his public profession of the Christian faith was that it not only stigmatized the latter religion as a force destructive of the old order in Xhosa society, but it also reshaped Kama's political image for the good of his religious life. He not only fled from the neighbourhood of his relations and sojourned in a strange land, but also reinforced the Colonial forces in the contemporary frontier struggles. His integrity, self-sacrifice and pro-Colonial inclination eventually won him Middledrift. Chapter four opens with Kama's settling in Middledrift. The theme here is two-pronged. It presents the 'Cattle-Killing' delusion as a source of new trials for the 'priest-chief', and at the same time exposes the Colonial Government's efforts to gain ascendancy above the Xhosa chiefs. Kama's land was the first testing ground in this respect, and the Chief was initially agreeable to the scheme. Chapter five alludes to instances of Chief Kama's unco-operative attitude as signs that his compromising spirit had its limits. An atmosphere of disregard towards Kama pervades the period. But the adversities that threatened to dominate his later life did not by any means shake his Christian principles and convictions. The traces of his good works may to this day be seen in Middledrift, the traditional home of the Kamas.
Keywords: Kama, William, 1798-1875; Shaw, William, 1798-1872; Methodist Church of Southern Africa -- Missions; Gqunukhwebe (African people) -- History; Wesleyville mission; Gqunukhwebe (African people) -- Kings and rulers; South Africa -- History -- Frontier Wars, 1811-1878; South Africa -- History -- Xhosa Cattle-Killing, 1856-1857; Converts -- South Africa; Cape of Good Hope (South Africa) -- Politics and government